The weight of African native-centric ecology in eco-desacralization - Ikechukwu Monday Osebor (Revista Bioética)
Abstract The ecological crisis is one of the environmental issues affecting the planet, and it is caused by eco-desacralization, a concept defined by environmental skepticism that relegates the divine identities of the environment. Doubts about the authenticity of environmental degradation or climate change and desert encroachment bear a strong anthropocentric view of nature. Skepticism may have deepened the human understanding of the natural world, but it has also destroyed the environment. In this study it is argued that eco-desacralization is environmental avarice, and steps must be taken to shift the strong anthropocentric perception of the natural world. To overcome this, we unearth African conservation ethics, deeply rooted in native-centric ecology. This concept reconstructs negative attitudes for the benefit of humanity. This study concludes that the resacralization of the environment by the teaching and learning of native-centric ecology in schools can mitigate the impacts of the ecological crisis.